Masa Depan Pendidikan Islam di Indonesia: Tantangan, Peluang, dan Strategi Transformasi Menuju Indonesia Emas 2045: Penelitian - Syukron Jamal (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Islamic education in Indonesia holds a pivotal role in nation-building, integrating religious values with modern scientific knowledge to shape well-rounded individuals who are competitive in a global era. Nevertheless, Islamic education continues to face fundamental challenges, including limited funding, infrastructure disparities, uneven quality of educators, and public perceptions that often position Islamic educational institutions as a secondary alternative compared to general education. This study aims to analyze the dynamics of Islamic education in Indonesia, identify the challenges it faces, and explore opportunities for transformation towards adaptive, responsive, and globally competitive education. The research method employed is literature review by examining various scholarly sources, official reports, and recent statistical data. The findings indicate that, despite structural and cultural obstacles, Islamic education possesses significant potential for transformation, supported by growing public trust and the forthcoming demographic bonus, which will heighten the demand for high-quality, character-driven human resources. The transformation of Islamic education is expected to contribute substantially to realizing the vision of Indonesia Emas 2045, by producing generations who are not only intellectually capable but also grounded in moral integrity, serving as a strong foundation for a sovereign and advanced nation.